Hubungan Pola Makan Dengan Kejadian Anemia Pada Ibu Hamil Di Wilayah Kerja Puskesmas Penajam - Yazah, Vira Firda; Rahman, Gajali; Lushinta, Lidia (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
Anemia in pregnancy was the condition of the mother withÂ hemoglobin level under 11 g%. A balanced diet consists of various types of food in appropriate amounts and proportions to meet a person's nutritional needs. This study aimed to determine the relationship between diet and the incidence of anemia in pregnant women on June 15-29 2022 in the Working Area of the Penajam Health Center. Thetype of this quantitative research was analytic observational with cross sectional approach. The population in this study were pregnant women in trimesters 1, 2 & 3 as well as pregnant women who had an examination at the Penajam Health Center, with sample of 50 pregnant women using simple random sampling technique. The results showed that there was a significant relationship between diet and the incidence of anemia in pregnant women (p-value = 0.001) with = 0.05. Diet in pregnant women will affect the incidence of anemia, the better the diet in pregnant women, the smaller the risk of anemia. There was a relationship between diet and the incidence of anemia in pregnant women